Serial thrombin generation and exploration of alternative anticoagulants in critically ill COVID-19 patients: Observations from Maastricht Intensive Care COVID Cohort - van de Berg, Tom W.; Mulder, Mark M. G.; Alnima, Teba; Nagy, Magdolna; van Oerle, Rene; Beckers, Erik A. M.; Hackeng, Tilman M.; Hulshof, Anne-Marije; Sels, Jan-Willem E. M.; Henskens, Yvonne M. C.; van der Horst, Iwan C. C.; ten Cate, Hugo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: COVID-19 associated coagulopathy (CAC) is associated with an increase in thromboembolic events. Current guidelines recommend prophylactic heparins in the management of CAC. However, the efficacy of this strategy in the intensive care population remains uncertain. Objective: We aimed to measure thrombin generation (TG) to assess CAC in intensive care unit (ICU) patients receiving thromboprophylaxis with low molecular weight heparin (LMWH) or unfractionated heparin (UFH). In addition, we performed statistical modelling to link TG parameters to patient characteristics and clinical parameters. Lastly, we studied the potency of different anticoagulants as an alternative to LMWH treatment in ex vivo COVID-19 plasma. Methods: We included 33 patients with confirmed COVID-19 admitted at the ICU. TG was measured at least twice over the course of 6 weeks after admission. Thrombin generation parameters peak height and endogenous thrombin potential (ETP) were compared to healthy controls. Results were subsequently correlated with a patient characteristics and laboratory measurements. In vitro spiking in TG with rivaroxaban, dabigatran, argatroban and orgaran was performed and compared to LMWH. Results: Anti-Xa levels of all patients remained within the therapeutic range throughout follow-up. At baseline, the mean (SE) endogenous thrombin potential (ETP) was 1727 (170) nM.min and 1620 (460) nM.min for ellagic acid (EA) and tissue factor (TF), respectively. In line with this we found a mean (SE) peak height of 353 (45) nM and 264 (96) nM for EA and TF. TG parameters remained elevated despite thromboprophylaxis. In vitro comparison of LMWHs and direct thrombin inhibitors (e.g. agratroban, dabigatran) revealed a higher efficacy in reducing coagulation potential for direct thrombin inhibition in both ellagic acid (EA) and tissue factor (TF) triggered TG. Conclusion: In a sub-group of mechanically ventilated, critically ill COVID-19 patients, despite apparent adequate anti-coagulation doses, thrombin generation potential remained high during ICU admission independent of age, sex, body mass index, APACHE II score, cardiovascular disease, and smoking status. These observations could, only partially, be explained by (anti)coagulation and thrombosis, inflammation, and multi-organ failure. Our in vitro data suggested that direct thrombin inhibition compared with LMWH might offer an alternate, more effective anticoagulant strategy in COVID-19.